COVID-19 patients in the operating room: a concise review of existing literature - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2021)
A novel Coronavirus was identified in late 2019 as the cause of COVID-19 disease which is highly contagious. SARS-CoV-2 is a single-stranded RNA, enveloped virus from the beta Coronavirus family. Intraoperative management of patients with COVID-19 is a high-risk procedure. An international attention has raised to develop recommendations for the management strategies. This review article was designed to synthesize the existing evidence and experience related to intraoperative management of COVID-19. This review provides a summary of clinical guidance and addresses six domains: principles of intraoperative monitoring, airway management and related difficulties, ventilation, type of anesthesia, medications and side effects, and intraoperative fluid management.
Keywords: COVID-19; SARS-CoV-2; Operating rooms; ANESTHETIC MANAGEMENT; CHINESE SOCIETY; TRANEXAMIC ACID; CORONAVIRUS; PNEUMONIA; MORTALITY; AIRWAY